1988
DOI: 10.1590/s0071-12761988000100013
|View full text |Cite
|
Sign up to set email alerts
|

Reinício da atividade ovariana no pós-parto em vacas holandesas do rebanho da ESALQ

Abstract: Foram determinados os perfis de progesterona no leite desnatado, em 32 vacas da raça Holandesa no pós-parto até a primeira ovulação no período de 1986 e 1987. A linha divisória das fases folicular e luteínica dos teores de progesterona foi estimada em l,12mg/ml. Ficou evidenciado que não há diferença no tempo da primeira ovulação no pós-parto (36,83 ± 18,92 dias) para vacas holandesas criadas em clima tropical ou temperado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Open day values were 179.28 ± 13.83; 226.34 ± 13.83; 236.88 ± 13.83; 211.94 ± 13.83. Results obtained with dairy cattle in Brazil (MEIRELLES et al, 1990) showed open day values of 151. A period of 100 days can be considered acceptable according some authors (FERREIRA & SÁ, 1986).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Open day values were 179.28 ± 13.83; 226.34 ± 13.83; 236.88 ± 13.83; 211.94 ± 13.83. Results obtained with dairy cattle in Brazil (MEIRELLES et al, 1990) showed open day values of 151. A period of 100 days can be considered acceptable according some authors (FERREIRA & SÁ, 1986).…”
Section: Resultsmentioning
confidence: 98%
“…Calving intervals of 12 -13 months are considered optimum under temperate condition (FERREIRA & SÁ, 1986). However the calving interval values can be misleading, since the calculation is based on those cows exhibiting successive parturitions, thus giving no indication of the proportion that fails to conceive (MEIRELLES et al, 1990). A more accurate indication of herd reproductive performance might be the number of open days, provided that it is calculated using the actual days from parturition to conception for cows which became pregnant and a value of 365 days is given to all those which did not successfully remate for a year or more after calving.…”
Section: Resultsmentioning
confidence: 99%